1998
DOI: 10.1037/0893-3200.12.4.459
|View full text |Cite
|
Sign up to set email alerts
|

Measuring parental attributions: Conceptual and methodological issues.

Abstract: A selective review is offered of current issues and new developments in the measurement of parental attributions for social behavior. Attributions have alternatively been conceptualized as involving (a) memory-dependent knowledge structures (i.e., interpretive styles that are dependent on the parent's history) or (b) stimulus-dependent appraisal processes (i.e., interpretations that are dependent on information available in the immediate context). Consideration is given to the theoretical underpinnings of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
125
0
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(134 citation statements)
references
References 106 publications
(127 reference statements)
3
125
0
6
Order By: Relevance
“…An important question is whether this bias is expressed in teachers' actual interactions with the child, or only in their perceptions of these interactions. It is reasonable to assume that attributions influence teachers' reactions, and hence the quality of their actual interactions with children in the long run (see for a similar argument with respect to parent-child relationships, Bugental, Johnston, New, & Silvester, 1998). Unfortunately, we were unable to examine this because we did not have any objective measures (e.g., observations) of these interactions.…”
Section: Discussionmentioning
confidence: 99%
“…An important question is whether this bias is expressed in teachers' actual interactions with the child, or only in their perceptions of these interactions. It is reasonable to assume that attributions influence teachers' reactions, and hence the quality of their actual interactions with children in the long run (see for a similar argument with respect to parent-child relationships, Bugental, Johnston, New, & Silvester, 1998). Unfortunately, we were unable to examine this because we did not have any objective measures (e.g., observations) of these interactions.…”
Section: Discussionmentioning
confidence: 99%
“…However, physicians with unrealistically high levels of perceived control may be problematic and potentially Predicting empathy judgments 19 dangerous in clinical settings. Further research could therefore consider how physician perceived control develops, the circumstances under which it operates automatically, and how it relates to moment-to-moment appraisal of ongoing medical events (Bugental et al 1998). A better understanding of physician perceived control may help to tailor medical training more effectively to individual needs.…”
Section: Insert Tables One and Two About Here Predicting Empathy Judgmentioning
confidence: 99%
“…Studies have found that low-perceived control [LPC] individuals are more reactive to challenging interactions, and act in ways that seek to reassert control and increase their feelings of efficacy (Bugental, Johnston, New & Silvester, 1998). For example, Kipnis, Schmidt, Price and Stitt (1981) found that LPC managers tended to impose solutions, exert control and delegate less to subordinates in order to regain control, maintain self-esteem and maximize feelings of efficacy.…”
mentioning
confidence: 99%
“…U poznatoj studiji ove vrste, koja se zbog longitudinalnog pristupa smatra jednom od metodološki najkorektnijih, majčine disciplinske mere su figurisale kao medijatori između njenih hostilnih atribucija i disciplinskih problema dece u školi (Nix et al, 1999). Nalazi studije pokazuju da majčine hostilne atribucije pouzdano predviđaju probleme u ponašanju dece u školi, otuda što ovakve tendencije indukuju ljutnju i oštre disciplinske postupke, što je potvrđeno i u nekim drugim istraživanjima (Bugental, Johnson, New, & Sylvester, 1998;Snyder, Cramer, Afrank, & Patterson, 2005). Nadalje, od svih disciplinskih mera, fizičko i verbalno kažnjavanje u najvišem stepenu predviđaju problematično ponašanje dece, pri čemu preovlađujući vaspitni stilovi i očekivanja roditelja ostvaruju medijatorsku ulogu u ovim relacijama (Brenner & Fox, 1998).…”
Section: Istraživanja čInilaca šKolske Nedisciplineunclassified